Forced Land Acquisition, Indigenous People and International Human Rights Obligations: A Study of Pakistan Legal Framework - Sannan Ali Shah (Al-Amīr Research Journal for Islamic Studies, 2025)
The process of the State acquiring the land compulsory is still regarded as one of the most disputable practices of the sovereign authorities which rather leads to the conflict between development requirements and the preservation of the basic human rights. This research paper is the critical analysis of the correspondence of the Land Acquisition Act to the international human rights norms especially the norms provided in the International Covenant on Civil and Political Rights (ICCPR) and the International Covenant on Economic, Social and Cultural Rights (ICESCR). It assesses the sufficiency of the Act in protecting constitutional rights to property, the right to life, livelihood and housing and the rights of vulnerable, marginalized communities, such as indigenous people and minorities. The paper holds that although the Act offers a legal framework of land acquisition, it does not meet the global human rights requirements because of poor procedural protection, compensation systems, and poor consideration of social and cultural rights. The attachments that indigenous peoples have to their territories and resources, which they struggle to maintain against the exploitation by wealthier external entities and government- sponsored land acquisitions. Indigenous People Often accompanied with insufficient compensation, these acquisitions displace indigenous communities from their ancestral and spiritually important territories. The paper questions whether indigenous peoples’ rights and interests are sufficiently safeguarded during such processes. Key words: Indigenous People; Land Acquisition; Public Purpose; Compensation, ICCPR, ICESCR